The Scottish Referendum: The View from Italy and Sardinia. Issue 3 (August 2014) - Ruggiu, Ilenia
<x xml:space="preserve">Abstract</x> Although there is little close understanding of Scotland's referendum in Italy, the fact of the referendum, and its result, are of great symbolic importance in current developments as to centre-region relations. Just as 'devolution' resonated in Italian politics in the 1990s, not least in the rise of the Lega Nord, so 'independence' has fuelled campaigns in a number of regions towards greater autonomy or outright secession. This article reviews the contemporary moves in various regions towards redefining (or breaking) their relationship with 'Italy', focussing particularly on the Sardinian case.